Ophthalmic Oncology - Esmaeli, Bita.; SpringerLink (Online service) (Boston, MA : Springer US : Imprint: Springer, 2011)
Ophthalmic Oncology explores the unique aspects of oncologic ophthalmology as a medical and surgical discipline practiced at a comprehensive cancer center. Multi-disciplinary management of ocular, orbital and adnexal cancers are highlighted using simple and tried-and-true algorithms. In addition, ocular problems caused as a direct result of cancer treatment are reviewed using illustrative photographs and case presentations. The content is provided by full-time ophthalmology faculty and fellows at M.D. Anderson Cancer Center. Experts in complementary disciplines such as ophthalmic pathology, dermatopathology, radiation oncology, radiology, and other surgical subspecialties, bring a novel perspective to each chapter. Clinical photographs and case presentations help clinicians, practicing general ophthalmologists, orbital and oculoplastics specialists, medical and surgical oncologists, and ophthalmology residents and fellows to correctly diagnose cancers of the orbit, eye, and adnexal structures, initiate appropriate management, as well as recognize and treat common ocular complications of cancer therapy.
Orbital and Adnexal Oncology -- Primary orbital tumors -- Metastatic orbital tumors -- Orbital tumors extending from periocular structures (brain, paranasal sinuses) -- Lacrimal gland tumors -- Primary eyelid cancers -- Conjunctival tumors -- Intraocular Tumors -- Retinoblaastoma -- Uveal melanoma -- Intraocular lymphoma -- Uveal metastatic lesions -- Retinal vascular tumors -- Ocular Surface Disease and Cornea -- Graft-vs-Host disease -- Cataract surgery in cancer patients -- Radiation-induced ocular surface disease -- Neuro-ophthalmic manifestations of Cancer -- Cranial neuropathies -- Skull based tumors -- Optic nerve tumors -- Leptomeningeal disease -- Cancer-associated retinopathy -- Neurofibromatosis -- Other optic nerve maladies in cancer patients -- Oculoplastic Surgery and Periocular Reconstructive Surgery in Cancer Patients -- Eyelid defects -- Nasolacrimal duct blockage/ Lacrimal surgery -- Eyelid malposition -- Orbital reconstruction -- Enucleation /evisceration /exenteration / orbital implants -- Surgical rehabilitation in the periocular region after facial nerve paralysis -- Ocular Side Effects of Cancer Therapy -- Lacrimal and canalicular toxicity -- Corneal toxicity -- Chemo-induced retinal toxicity and optic neuropathy -- Orbital and periorbital side effects -- Radiation toxicity -- Ocular and orbital infections in the immune compromised host -- Vitreoretinal Conditions in Cancer Patients -- Endogenous endophthalmitis -- Viral retinitis -- Diagnostic vitrectomy in cancer patients.
Keywords: Medicine; Oncology; Ophthalmology; Medicine & Public Health; Oncology; Ophthalmology